Linier Perturbation Method Analytic Shear Wave Propagation In A Dispersive Medium (Pendipa)
This research was based on showing how the relationship of the perturbation method to the wave function entering the dispersive medium area. Disperse medium is a medium where when the wave enters the area, it experiences changes in wave shape and wave energy. The purpose of this study is to show how the perturbation method can be reduced to a term that is still linear with the assumption that the next term is very small so that the wave term is still linear to the wave change. This research is qualitative research. The place of this research is at the TD Pardede Institute of Science and Technology. From the analysis in this study, it was found that the wave experienced a decreasing intensity towards the depth of the dispersive medium with the assumption that the attenuation coefficient ( ) was still continuous along the depth of the material passed by the wave. In the case of seismic waves when the wave moves through the medium, its intensity decreases with distance. The presence of disturbances in the layer passed by the wave causes the shift of the material to experience a disturbance characteristic where the wave amplitude is getting smaller. This is because the absorption of wave energy by the particles of the dispersive medium continues to experience attenuation.